2016
DOI: 10.5812/ircmj.21096
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Assertiveness Training on the Levels of Stress, Anxiety, and Depression of High School Students

Abstract: Background:Adolescence is a transition period from childhood to early adulthood. Because of the immense pressure imposed on adolescents due to the complications and ambiguities of this transition, their level of excitement increases and sometimes it appears in the form of sensitivity and intense excitement.Objectives:This study aimed at determining the effectiveness of assertiveness training on the levels of stress, anxiety, and depression of high school students.Materials and Methods:This quasi-experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 23 publications
0
29
0
7
Order By: Relevance
“…Experts believe that depression is relieved when individuals reduce their extreme focus on themselves (45). A recent study also suggested that interpersonal skills and assertiveness training could reduce depression, anxiety, and stress (46). Several limitations of this investigation need to be mentioned.…”
Section: Discussionmentioning
confidence: 85%
“…Experts believe that depression is relieved when individuals reduce their extreme focus on themselves (45). A recent study also suggested that interpersonal skills and assertiveness training could reduce depression, anxiety, and stress (46). Several limitations of this investigation need to be mentioned.…”
Section: Discussionmentioning
confidence: 85%
“…21 The main aim of assertiveness training is to teach individuals that they have basic human rights and how they can keep their rights without violating others' rights. 23,35 The assertiveness training program aims to increase self-confidence, self-esteem, and selfperception, to express feelings and thoughts adequately, to improve assertiveness and social communication skills, to reduce concerns about communication, to improve social functioning and ultimately improve life satisfaction and coping skills. 21,22,35,36 Assertiveness training is thought to be more effective in small groups and it is recommended that the training curriculum be conducted between 6 and 12 sessions in total and in 2 to 3 sessions per week for 45 to 90 minutes each.…”
Section: Assertiveness Training Programmentioning
confidence: 99%
“…23,35 The assertiveness training program aims to increase self-confidence, self-esteem, and selfperception, to express feelings and thoughts adequately, to improve assertiveness and social communication skills, to reduce concerns about communication, to improve social functioning and ultimately improve life satisfaction and coping skills. 21,22,35,36 Assertiveness training is thought to be more effective in small groups and it is recommended that the training curriculum be conducted between 6 and 12 sessions in total and in 2 to 3 sessions per week for 45 to 90 minutes each. 23,27 The assertiveness training was applied to 30 patients in the experimental group consisting of three groups of 10 persons each, with 1 day in each week, and 90 minutes (45 + 45 minutes) for each session, and for eight sessions in total.…”
Section: Assertiveness Training Programmentioning
confidence: 99%
“…Atılganlık eğitimi-nin bireylerin benlik saygılarını arttırdığı, karar verme becerilerini geliştirdiği ve olumsuz duygulanımlarını azalttığı, atılganlık ve özgüveni yükselttiği belirtilmektedir. [13,25,32] Araştırmanın bazı sınırlılıkları bulunmaktadır. Araştırmanın bulguları yalnızca çalışmanın yapıldığı evrene genellenebilir.…”
Section: Verilerin Analiziunclassified
“…Atılgan davranış özellikleri bireye kazandırıldığında hak ihlalleri daha az görülmekte ve sorunlar daha kolay çözümlenmektedir. [13] Araştırma okul çağı çocuklarının akran zorbalığı durumları ile atılganlık düzeyleri ve ilişkili faktörleri belirlemek amacıyla yapılmıştır. Bu amaç doğrultusunda aşağıdaki sorulara yanıt aranmıştır:…”
unclassified